pengaruh kepuasan dan kepercayaan green product pertamax ron 92 terhadap keputusan pembeliandi pertashop olak kemang - Hoirul Tamimi; Titin Agustin Nengsih; Nurlia Fusfita; Munsarida Munsarida (Program Studi Manajemen Keuangan Syariah, 2023)
The purpose of this study was to analyze the purchasing decisions at Pertashop Olak Kemang on the influence of satisfcation and trust. This research was conducted based on the current phenomenon, namely Pertamax RON 92 sales have decreased in the period November 2021 to October 2022. The subjects of this study were consumers of Pertamax RON 92. The samples in this study consisted of 100 renspondents distributed using the questionnaire survey method, then processed using multiple linear regression method. The results of this study partially the satisfaction variable and the trust variable jointly influence the purhasing decision at the Olak Kemang shop. From the results of the study simultaneously the satisfaction variable and the trust variable together have a significant effect on purchasing decisions at the Pertashop Olak Kemang.Keywords: Satisfaction, Trust, Purchasing Decisions.